Pengaruh Faktor Pendukung terhadap Perilaku Masyarakat dalam Pencegahan Penyakit Filariasis di Kota Semarang - Ariska Tri Hapsari; Zahroh Shaluhiyah; Antono Suryoputro (Master Program of Health Promotion Faculty of Public Health Diponegoro University, 2018)
Background: Filariasis is chronic infectious disease due to filariasis worm infection which transmitted through mosquitoe bites. There were 241 districts as filariasis endemic districts in Indonesia. More than 50% of the population in endemic areas are potential to contract with this disease. High prevalence of filariasis cases, can cause the increasing mortality cases if the disease did not treat it properly and prevent it early. There were 21 new cases found and three cases of them have died. This study aims to analyze the supporting factors influence to prevention behaviour of filariasis.Method: This study is a quantitative study with a cross sectional design involved 178 respondents as total sampling. The people who live surrounding the filariasis sufferer (≤ 100m) were recruited as a sample. Data collected using face to face interview by standard questionnaire. Data were analyzed using univariate, Chi-square test and multiple logistic regression.Results: The results shows that the support of family, neighbors, and community leaders were not significant associated to the filariasis preventive behavior of respondents (P value> 0.05) while the support of health workers and the exposure of health promotion programs were significant associated the filariasis prevention behavior of the respondents. According to multivariate analysis, exposure on health promotion programs and supporting from health provider influenced the prevention behaviour of respondents with Odds Ratio 11.237 and p value 0.023. The role of health providers in the prevention programs to the community was greatly important to improve knowledge, attitude, and people behaviour to prevent this disease. To reduce disease incidence is needed community empowerment program to improve community participation in preventing disease.Keywords: filariaris, supporting factors, behaviour of preventing filariasis